A qualitative exploration of parental experiences of stigma while living with HIV in Bangladesh. Issue 2 (1st February 2016) - Islam, Md Shahidul; Scott, John; Minichiello, Victor
ABSTRACT: With much of the focus on the "risk" groups, families have often been less studied in HIV research. Further, because of a focus on the aetiology and epidemiology of HIV, the social impacts associated with HIV on families and neighbours are sometimes overlooked. This study examined parental experiences of stigma and discrimination while living with HIV within a family context in Bangladesh. A qualitative research design using a grounded theory approach was used for this research. Data was collected through in-depth interviews with 19 HIV-positive parents, recruited with the support of two self-help groups of HIV-positive people, in two settings namely Khulna and Dhaka in Bangladesh. The findings indicate that HIV-positive parents held the view that they continue to experience significant stigma and their narratives clearly show how this affected them and their children. A range of informal practices were enacted in everyday contexts by extended family and community members to identify, demarcate and limit the social interaction of HIV-positive parents. Parents highlighted a number of factors including negative thoughts and behaviours, rejection, isolation and derogatory remarks as manifestations of stigma and discrimination, impacting upon them and their children because of their association with HIV.